2016
DOI: 10.3748/wjg.v22.i23.5422
|View full text |Cite
|
Sign up to set email alerts
|

Endocan-expressing microvessel density as a prognostic factor for survival in human gastric cancer

Abstract: Endocan-MVD significantly correlates with the expression of VEGF and VEGFR2 and is a valuable prognostic factor for survival in human gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 24 publications
0
32
0
3
Order By: Relevance
“…Endocan was shown to act both as a target and modulator of VEGF signalling, as shown by reduced vascular outgrowth and VEGF signaling in the retina of Esm1 knock-out mice [25]. In recent years, endocan has been investigated as a marker of neoangiogenesis [47], and its overexpression, especially within the endothelial cells of tumour vessels, as well as higher circulating endocan levels, have been associated with poor prognosis in malignant tumours, such as breast cancer, non-small cell lung cancer, gastric cancer and hepatocellular carcinoma [21][22][23]48]. According to previous reports, the expression of endocan in PitNETs was found to be associated with invasion of the cavernous sinus [11,12] and higher risk of recurrence [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endocan was shown to act both as a target and modulator of VEGF signalling, as shown by reduced vascular outgrowth and VEGF signaling in the retina of Esm1 knock-out mice [25]. In recent years, endocan has been investigated as a marker of neoangiogenesis [47], and its overexpression, especially within the endothelial cells of tumour vessels, as well as higher circulating endocan levels, have been associated with poor prognosis in malignant tumours, such as breast cancer, non-small cell lung cancer, gastric cancer and hepatocellular carcinoma [21][22][23]48]. According to previous reports, the expression of endocan in PitNETs was found to be associated with invasion of the cavernous sinus [11,12] and higher risk of recurrence [9].…”
Section: Discussionmentioning
confidence: 99%
“…Endocan is an endothelium-derived proteoglycan involved in cell adhesion and neoangiogenesis. Although endocan is also expressed in normal tissues [20], the expression of endocan and its circulating levels are positively associated with a worse prognosis and poor survival in various cancers [21][22][23]. Interestingly, endocan has been shown to enhance the adhesion between monocytes and endothelial cells [24], and Esm1 knock-out mice show decreased vascular permeability and leucocyte extravasation [25], suggesting that endocan expression in endothelial tumour cells could potentially facilitate the trafficking of immune cells to the tumour microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…It is not accompanied by an effective immunological response. The contemporary process of neo-lymphoangiogenesis represents a direct consequence [22][23][24][25]. We hope that in a near future, the classification and staging of each gastric tumor case will include its immunological characterization, a complete study of its lymphatic apparatus, and of the immune response [26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ESM-1 plays a role in angiogenesis and inflammation. Numerous studies have demonstrated that ESM-1 can be used as a potential biomarker for detection in gastric cancer 36 , bladder cancer 37 , colorectal cancer 28 , hepatocellular carcinoma 38 , pituitary adenoma 39 , ovarian cancer 40 , breast cancer 41 , and acute leukemia 20 , but ESM-1 has not been investigated in OSCC.…”
Section: Discussionmentioning
confidence: 99%